Histopathological study of cecal tonsils in broilers exposed to heat stress after treatment with lactobacillus acidophilus: Balqees, H. A.; Ebtasam, J. A. and Nawals, J. - Ebtasam, J. A., Balqees H. A.; (The Iraqi Journal of Veterinary Medicine, 2015)
This study was designed to investigate the effect of Lactobacillus spp on the histology of cecal tonsils in broiler chicks exposed to heat stress. eighty broiler chicks were divided randomly into four groups equally and treated as follows: 1st group was administred orally with 1×108/0.1 CFU/ml of (L.B.) at one day old, 2nd group was treated as 1st group but at 21 days old, and 3rd group (control positive), all three groups were exposed to heat stress (38-40Cº) for period 10 days for three hours continuously, 4th group (control negative) was kept under natural condition. Organ samples from cecal tonsils were taken for histopathological test after 48 hrs., 120 hrs. and 240 hrs. of exposure to heat stress. The result revealed that most important lesions in 3rd group occur after 48 hrs. Cellular debri and marked cellularity (inflammatory cell) occur after 120hrs. was vacculation and degeneration of epithelial layer cell. While the first 1st group after 48 hrs. showed moderate cellularity, after 120 hrs. showed marked lymphocyte proliferation and after 220 hrs. Increased goblet cell in the epithelial cell and 2nd group showed after 48 hrs. mild cellarity of lamina properia, and after 120 hrs. showed moderate lymphocytic hyperplasia. In conclusion exposure to heat stress caused destructive lesion in the cecal tonsil especially after 48 hrs. and 120 hrs. and gave lactobacillus acidophilus at 21 days more effective that at one day in reducing the effect of heat stress on histology of cecal tonsils.